2009
DOI: 10.1177/0009922809332682
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Tolerance of Healthy Term Infants Receiving Hydrolyzed Infant Formulas Supplemented With Lactobacillus rhamnosus GG: Randomized, Double-Blind, Controlled Trial

Abstract: Healthy, term infants received extensively hydrolyzed casein formula (EHF; control), the same formula supplemented with Lactobacillus rhamnosus GG (EHF-LGG), or partially hydrolyzed whey:casein (60:40) formula supplemented with LGG (PHF-LGG), in this double-blind, randomized, controlled, parallel, prospective study. Anthropometric measures and 24-hour dietary and tolerance recalls were obtained at 30, 60, 90, 120, and 150 days of age. Blood collected in a subset of infants was analyzed for fatty acid profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 39 publications
4
56
0
2
Order By: Relevance
“…16 In seven studies there was either exclusive formula feeding from birth in all randomised participants [17][18][19][20][21][22] or total cessation of breastfeeding by 14 days. 23 In five studies, randomisation and allocation of formula milk occurred early: during pregnancy, 24 at birth in all 25 26 or some 27 participants, or in the first four days after birth in most participants. 28 In one study, infants were enrolled on day one, and over half were exclusively formula fed, 29 and in another breast milk was purposefully withheld for the first three days of life in some infants.…”
Section: Decreased Riskmentioning
confidence: 99%
“…16 In seven studies there was either exclusive formula feeding from birth in all randomised participants [17][18][19][20][21][22] or total cessation of breastfeeding by 14 days. 23 In five studies, randomisation and allocation of formula milk occurred early: during pregnancy, 24 at birth in all 25 26 or some 27 participants, or in the first four days after birth in most participants. 28 In one study, infants were enrolled on day one, and over half were exclusively formula fed, 29 and in another breast milk was purposefully withheld for the first three days of life in some infants.…”
Section: Decreased Riskmentioning
confidence: 99%
“…Growth and other nutrition parameters, including circulating fatty acid levels, were demonstrated to be normal in healthy term infants who received this formula up to 4 months of age 23. Available data suggest that the LGG-supplemented EH casein formula assessed in the current study provides additional benefits of better management of allergic colitis, as well as faster tolerance acquisition, in infants with CMA that are not observed with the non-supplemented formula.…”
Section: Discussionmentioning
confidence: 67%
“…Lactobacillus rhamnosus GG (LGG) is the most studied probiotic, with demonstrated benefits when added to an EH formula, including decreased severity of atopic dermatitis (AD),18 19 reduced intestinal inflammation18 20 and faster induction of tolerance21 in infants with CMA and improved recovery from allergic colitis 20. We previously demonstrated that LGG was well tolerated, promoted normal growth and transiently colonised the intestine when added to an EH casein formula fed to healthy term infants 22 23. An EH formula with the same casein hydrolysate and many years of clinical experience of safety use in children with CMA was demonstrated to be hypoallergenic in those children in a DBPCFC trial 13.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies were performed with different infant formulas containing OSA-modified starch at levels similar to the proposed use levels (up to 20 g/L). [94][95][96][97][98] The formulas were the sole source of nutrition for infants starting to feed from birth to 16 days of age and were administered for periods of 28-120 days. All studies demonstrated that formulas containing OSA-modified starch were well tolerated and supported normal healthy growth, with no health concerns reported.…”
Section: Nutritional Considerationsmentioning
confidence: 99%